The influence of the electron beam treatment on aluminum and iron nanopowders - Badamasi N. M. (Теплофизические аспекты энергетических технологий, 2023)
This work involves the differential thermal analysis of iron and aluminum nanopowders irradiated with electron beam of energy of 360 keV within 120 ns. The Differential Thermal Analysis of the irradiated samples reveals an increase in the amount of water particles absorbed by the surface of the nanoparticles, as well as the accumulation of defects inside the core of their crystal structure.